A review of sodium diclofenac as a potential medicament to eliminate Enterococcus faecalis in regenerative endodontic treatment - Prasetyo, Eric Priyo; Yuanita, Tamara; Setyabudi; Bin Sharizal, Shafy Shariz; Sukandar, Wilson; Paidal, Nurfahira; Charles, William; Christabel, Phebe Fedora; Liong, Michelle; Prasetyaningtias, Silvia Arlita Hayu (Universitas Airlangga, 2024)
Background: Traumatic dental injuries often occur in the community reaching 85% of patients and in preschool children the proportion reaches 17%. Among the injuries are tooth fracture, tooth luxation, tooth avulsion and open apex which causes pulp death or necrosis, causing root growth to stop. Regenerative endodontic treatment (RET) with a biological approach to treat necrotic immature permanent teeth can promote pulpal growth, increase the thickness of the dentin wall and form apical foramens. Enterococcus faecalis bacteria can be resistant to some drugs and root canal irrigation substances and may persist in the root canal system. Recently, sodium diclofenac has been reported to retain a new potential to eliminate Enterococcus faecalis biofilm. This shows that sodium diclofenac is potential as an anti-biofilm material. Purpose: To evaluate the potential use of sodium diclofenac in RET. Review: This review was investigated in PubMed and Google Scholar containing keywords: Sodium Diclofenac, Enterococcus faecalis and Regenerative Endodontic Treatment. Sodium diclofenac is a potential medicament to eliminate Enterococcus faecalis biofilm therefore has a potency to be used in Regenerative Endodontic Treatment. Conclusion: The success rate of RET depends on the elimination of microorganisms in the root canal systems. The use of sodium diclofenac as a medicament to eliminate Enterococcus faecalis biofilm is potential to be used in RET. Further researches are encouraged to explore the benefits of sodium diclofenac as a medicament in RET.